Magnetic Nanoparticles: Nanostructured Soft Matter with Magnetic Nanoparticles (Adv. Funct. Mater. 22/2016). (16th June 2016) - Tokarev, Alexander; Yatvin, Jeremy; Trotsenko, Oleksandr; Locklin, Jason; Minko, Sergiy
Abstract : Superparamagnetic nanoparticles have a wide range of applications in materials science and biomedicine, because of their unique response and manipulability under magnetic fields. On page 3761, S. Minko and co‐workers review the synthesis of functionalized magnetic nanoparticles, and discuss the various approaches for manipulation and assembly in uniform and nonuniform magnetic fields. Image credit: Ella Marushchenko.